2024
DOI: 10.3390/jcm13051353
|View full text |Cite
|
Sign up to set email alerts
|

Complete Blood Count (CBC)-Derived Inflammation Indexes Are Useful in Predicting Metabolic Syndrome in Adults with Severe Obesity

Alice Marra,
Adele Bondesan,
Diana Caroli
et al.

Abstract: Background: Metabolic syndrome (MetS) is a globally increasing pathological condition. Recent research highlighted the utility of complete blood count-derived (CBC) inflammation indexes to predict MetS in adults with obesity. Methods: This study examined CBC-derived inflammation indexes (NHR, LHR, MHR, PHR, SIRI, AISI, and SII) in 231 adults with severe obesity (88 males, 143 females; age: 52.3 [36.4–63.3] years), divided based on the presence (MetS+) or absence (MetS-) of MetS. The relationships between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In individuals with MetS, particularly when coupled with obesity, the continuous release of cytokines and adipokines from adipose tissue triggers an inflammatory cascade involving various immune system-related cells [31,32], like neutrophils, lymphocytes, monocytes, and macrophages [33,34]. In recent years, as an alternative to the standard markers of inflammatory status (i.e., IL-6, CRP, and adiponectin), an increasing body of research has indicated that biomarkers derived from peripheral blood cells, such as the Neutrophil/Lymphocyte Ratio (NLR) [14,35], Platelet/Lymphocyte Ratio (PLR) [36], Monocyte/Lymphocyte Ratio (MLR) [21], Aggregate Systemic Inflammation Index (AISI) [17], SIRI [12,15], and Systemic Immune-Inflammation Index (SII) [12,21], can serve as indicators for detecting and predicting the presence and severity of systemic inflammatory processes, including cardiovascular diseases and MetS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In individuals with MetS, particularly when coupled with obesity, the continuous release of cytokines and adipokines from adipose tissue triggers an inflammatory cascade involving various immune system-related cells [31,32], like neutrophils, lymphocytes, monocytes, and macrophages [33,34]. In recent years, as an alternative to the standard markers of inflammatory status (i.e., IL-6, CRP, and adiponectin), an increasing body of research has indicated that biomarkers derived from peripheral blood cells, such as the Neutrophil/Lymphocyte Ratio (NLR) [14,35], Platelet/Lymphocyte Ratio (PLR) [36], Monocyte/Lymphocyte Ratio (MLR) [21], Aggregate Systemic Inflammation Index (AISI) [17], SIRI [12,15], and Systemic Immune-Inflammation Index (SII) [12,21], can serve as indicators for detecting and predicting the presence and severity of systemic inflammatory processes, including cardiovascular diseases and MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, markers associated with HDL-C were also reported to serve as reliable indicators reflecting the degree of inflammation [15,17,19,21,[37][38][39][40]. Notably, alterations in lipid profiles among individuals with obesity include increases in serum total cholesterol, triglyceride, and LDL-cholesterol levels, coupled with a decrease in HDL-cholesterol levels [26,41,42].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations